A Scalable High-Performance I/O System for a Numerical Weather Forecast Model on the Cubed-Sphere Grid - Kim, Junghan; Kwon, Young Cheol; Kim, Tae-Hun (Asia-Pacific journal of atmospheric sciences, 2018)
The design and implementation of a high-performance Input/Output (I/O) library for the Korean Integrated Model (KIM, KIM-IO) is described in this paper. The KIM is a next-generation global operational model for the Korea Meteorological Administration (KMA). The horizontal discretization of KIM consists of the spectral-element method on the cubed-sphere grid. The KIM-IO is developed to be a consistent and efficient approach for input and output of essential data in this particular grid structure in a multiprocessing environment. The KIM-IO provides three main features, comprising the sequential I/O, parallel I/O, and I/O decomposition methods, and adopts user-friendly interfaces similar to the Network Common Data Form (NetCDF). The efficiency of the KIM-IO is verified using experiments to analyze the performance of its three features. The scalability is also verified by implementing the KIMIO in the KIM at a resolution of approximately 12 km using the 4th supercomputer of KMA. The experimental results show that both regular parallel I/O and sequential I/O undergo performance degradation with an increasing number of processes. However, the I/O decomposition method in the KIM-IO overcomes this degradation, leading to improvement in scalability. The results also indicate that with using the new I/O decomposition method, the KIM attains good parallel scalability up to Ο (100,000) cores.